ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY DENGAN PENGGUNAAN MODEL ECONOMIC PRODUCTION QUANTITY PADA BATIK SRIWEDARI DI SURAKARTA - Anggy Rahma Putri; Yohanes Djoko Suseno; Erni Widajanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study is to analyze the efficiency of controlling raw material inventory costs and analyze the differences in raw material inventory costs by using the Economic Order Quantity (EOQ) method and by using the Economic Production Quantity (EPQ) model compared to conventional methods on Sriwedari Batik in Surakarta. Based on the results of research that has been done, it can be concluded that the policies implemented by Batik Sriwedari in Surakarta have not yet reached the level of efficiency. The use of the EOQ method and the use of the EPQ model are able to regulate the inventory system and production system to be better, more measurable and reduce the total costs that must be incurred by the company.